Radiosynthesis and Quality Control of [18F] PSMA-1007 at the Cyclotron Facility of National Institute of Nuclear Medicine and Allied Sciences (NINMAS) for Diagnosis of Prostate Cancer - Uddin, Md Jashim; Anwar Ul Azim, Mohammad; Biswasarma, Sanchoy Chandra; Islam, Md Saiful; Islam, Sanjida; Mamun, Mustafa; Begum, Ferdoushi; Hossain, Md Nahid; Mia, Md Shohag; Mehdi, Hasan; et al. (Bangladesh Journal of Nuclear Medicine, 2024)
Radiolabeled tracers targeting prostate-specific membrane antigen (PSMA) have revolutionized PET imaging for prostate cancer diagnosis. Here, we present the inaugural production and quality control assessment of (18F) PSMA-1007 at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Bangladesh. The synthesis, conducted via a one-step procedure, yielded remarkable radiochemical yields (46.85%) with synthesis time 40 minutes. Quality control measures adhered to European Pharmacopoeia standards, enabling clinical deployment across Nuclear Medicine and PET-CT centers in Bangladesh. This pioneering effort marks a significant advancement in prostate cancer imaging within the region. Bangladesh J. Nuclear Med. 26(2): 198-200, 2023